Analysis of the Effectiveness of Healthcare M&A Transactions in Developed Countries - Nazarova, Varvara (Panoeconomicus, 2018)
The healthcare industry is a large and fast-growing segment of the corporate world, especially in developed countries. In the face of growing competition, healthcare companies inevitably resort to mergers and acquisitions (M&As) in order to accelerate their development. The objective of this study is to identify the creation of additional value for M&A deal participants in the healthcare industry in the United States and the European Union in 2008–2017. In this paper, we propose the following thesis statement: can healthcare companies expect excess returns from M&A deals? On average, M&A deals in the healthcare industry in developed countries create positive abnormal returns for acquiring companies and are efficient; a positive, significant impact on abnormal returns was found in the deal value of M&A deals, a negative significant impact was observed for deals conducted with the shares payment method and for acquiring companies with a larger number of employees. Key words: Merger and acquisition transactions, Strategy effectiveness, Average excess returns, Healthcare companies, Developed countries. JEL: G30, L1.